PERBANDINGAN HASIL ANALISIS POLA ALIRAN DENGAN PERSAMAAN RANS DAN LES DALAM COMPUTATIONAL FLUID DYNAMICS (CFD): LITERATURE RIVIEW - Elsy Thiansy; Tedy Agung Cahyadi; Shofa Rijalul Haq (Balai Besar Pengujian Mineral dan Batubara tekMIRA, 2025)
The settling pond functions to hold and settle suspended particles, especially Total Suspended Solid (TSS) in order to reduce the pollutant load. However, the effectiveness of settling ponds is greatly influenced by the flow characteristics and the concentration of tss carried. This research compares two numerical approaches in Computational Fluid Dynamics (CFD), namely Reynolds-Averaged Navier-Stokes (RANS) and Large Eddy Simulation (LES). Both of these methods are widely used in turbulent flow simulations, but have different approaches and levels of accuracy in representing turbulence structures. This study reviews various recent scientific publications that apply the rans and les equations in internal and external flow cases, including settling pond applications. The review results show that the RANS equation is suitable for large-scale engineering simulations with low computational requirements but is less accurate in capturing turbulence details. The les equation provides more accurate results in capturing turbulent flow patterns than the RANS model. However, tutoring models require greater computational resources, so they need to be considered for more complex applications. From this comparison it can be concluded that the selection of equations in a CFD is very dependent on the analysis objectives, limited computing resources, and the level of data detail required.